2020
DOI: 10.1017/s0954102020000541
|View full text |Cite
|
Sign up to set email alerts
|

A debris-covered glacier at Kerguelen (49°S, 69°E) over the past 15 000 years

Abstract: Debris-covered glaciers constitute a large part of the world's cryosphere. However, little is known about their long-term response to multi-millennial climate variability, in particular in the Southern Hemisphere. Here, we provide first insights into the response of a debris-covered glacier to multi-millennial climate variability in the sub-Antarctic Kerguelen Archipelago, which can be compared to that of recently investigated debris-free glaciers. We focus on the Gentil Glacier and present 13 new 36Cl cosmic-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…All detailed sample information is shown in Table I. The five new samples collected on the archipelago were shipped to the Centre de Recherche et d'Enseignement de Géosciences de l'Environnement (CEREGE) laboratory in Aix-en-Provence, France, where the basaltic whole-rock samples were prepared for in situ -produced 36 Cl CRE dating, following the same methods as those described in the online supplemental material of Charton et al (2020). The chemical compositions of the bulk rocks and the chemically treated sample fractions, which are needed to compute the exposure ages, are listed in Tables II and III.…”
Section: Methodsmentioning
confidence: 99%
“…All detailed sample information is shown in Table I. The five new samples collected on the archipelago were shipped to the Centre de Recherche et d'Enseignement de Géosciences de l'Environnement (CEREGE) laboratory in Aix-en-Provence, France, where the basaltic whole-rock samples were prepared for in situ -produced 36 Cl CRE dating, following the same methods as those described in the online supplemental material of Charton et al (2020). The chemical compositions of the bulk rocks and the chemically treated sample fractions, which are needed to compute the exposure ages, are listed in Tables II and III.…”
Section: Methodsmentioning
confidence: 99%
“…However, recent research has also shown that debris-covered glaciers can be more sensitive to climate variability than initially thought, as some features may respond rapidly to changes in temperature and precipitation (Charton et al, 2020). Therefore, when interpreting past glacial oscillations both climate changes as well as paraglacial processes must be taken into account.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%